Digitization of the scientific library of ZVO: current state and prospects - Berezhna, S.; Korobkina, O. (New Collegium, 2023)
The article is devoted to the issue of digitalization of scientific libraries of higher education institutions. The publications were investigating the current state and prospects of Ukrainian libraries digital transformation, university libraries were actually analyzed. It is proved that digitization determines the vector of development of the university library, significantly affects the model of library activity, the transformation of the traditional functions of the scientific library. There are some examples of storage and renewal of traditional library funds, and ensuring their availability with the help of digital technologies in the scientific library of Kharkiv National Pedagogical University named after H.S. Skovoroda. The areas of international cooperation and partnership with world libraries and institutions which are working in the field of digital technologies were analyzed. Special attention was paid to the possibility that scientists can use international databases Scopus, Web of Science, ScienceDirect, resources of the Research4Life platform in the libraries of higher education institutions. It is emphasized some advantages of digitalization of libraries of higher education institutions, such as: a convenient access to information for library users, increasing the range of library services, open access to the digitized rare and valuable publications, effective use of library space, wide use of library resources, increasing the amount of online library users. The role of the digital presence of the library of Kharkiv National Pedagogical University named after H.S. Skovoroda (electronic catalogue, electronic archive of the university, information and search resource "Scientometric profiles of scientists", etc.) in the educational and scientific space of the university has been specified. Ways of cooperation with Ukrainian libraries and institutions working in the field of digital technologies were considered. The effectiveness of popularizing scientific library resources through social networks has been proven. The importance of improving the efficiency of higher education libraries through changes to access information was emphasized.